Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels - Tin, Adrienne; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Krämer, Bernhard; März, Winfried (Nature genetics, 2019)
A trans-ancestry genome-wide association study of serum urate levels identifies 183 loci influencing this trait. Enrichment analyses, fine-mapping and colocalization with gene expression in 47 tissues implicate the kidney and liver as key target organs and prioritize potential causal genes.